Implementasi Pendidikan Karakter di Lingkungan SMPN 1 Karawang - Dhafa Frassetia Saputra; Ajat Rukajat; Khalid Ramdhani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of writing this article is to discuss the meaning and role of the educational environment in character education, as well as to minimize the dangers of complexity issues related to the decline of morality in the educational environment, to help achieve the national policy of character education for students in order to achieve their potential as human beings who believe and fear God. God Almighty, has noble character, is healthy, knowledgeable, capable, creative, independent, and becomes a responsible citizen. The analytical method used in the discussion of the main topic uses a causal effectual analysis model by reviewing the rational relationship, which analyzes the causal relationship between the educational environment in character education and the main source of the literature review. The results of the discussion show that the educational environment has a major influence in the formation of character education, and makes them have potential with positive values. So it can be concluded that to carry out character education needs to be supported by a good educational environment.